Pemetaan Kejadian Kasus Demam Berdarah Dengue di Kabupaten Kediri Tahun 2023 - Dwi Regina Istiqlala (Ficco Public Health Journal, 2024)
Background: The cases of dengue fever (DBD) in Indonesia show a fluctuating trend. DBD remains a public health issue because it affects all age groups and can lead to death. Efforts to control and prevent DBD are crucial to reduce its impact on the community. The purpose of this study is to illustrate the distribution pattern of DBD cases in Kediri Regency in the form of a map. Methods: This study uses a descriptive observational quantitative research design. The research analyzes secondary data obtained from the Kediri Regency Health Office using Geographic Information System (GIS). Data was collected from routine health reports and mapped to identify spatial patterns of DBD cases across the subdistricts. Results: The subdistrict with the highest DBD cases is Pare with the highest number of cases, totaling 106,968 cases, followed by Mojo subdistrict with 87,280 cases. The subdistrict with the lowest cases is Kunjang, with 32,641 DBD cases. The distribution pattern of these cases indicates areas with higher population density and environmental factors may contribute to the increased incidence in certain subdistricts. Conclusions: Optimal handling and prevention of DBD cases should be implemented to prevent an increase in DBD cases. Additionally, targeted interventions in high-risk subdistricts, such as Pare and Mojo, are essential to reduce the overall incidence of DBD.